RACIOCÍNIO LÓGICO NA EDUCAÇÃO BÁSICA: UTILIZAÇÃO DE PORTAS LÓGICAS NO ENSINO - IGOR GUSTAVO DA COSTA PASSETTI (2024)
Implementation of the new high school in Brazil, accompanied by the new norms and guidelines of the Base Nacional Comum Curricular - National Common Curricular Base – (BNCC), has led to the introduction of a range of elective subjects that go beyond the sphere of Basic General Education. These subjects aim to enhance and deepen the contents of the traditional curriculum, seeking to intensify students' knowledge in various areas of learning. When presented to students and incorporated into the curriculum schedule, these subjects allow students to choose specific areas of interest and knowledge deepening. One of these elective subjects is Logical Reasoning. This paper outlines a strategy employed for teaching this subject, aiming not only at consolidating knowledge by the student but also at providing playful stimulus to promote interest and motivation among students in this area of study. The present study offers a thorough analysis of Propositional Logic, structured through a pedagogical sequence developed by the author of this material. Additionally, guidelines are provided for the design of an experiment aimed at practicing the concepts of the truth table of two logical connectors: conjunction and disjunction. Guidelines for implementing this experiment in the classroom are also presented, according to the schedule and didactic sequence proposed in this study.